The dialogical and political nature of emotions: A reading of Vygotsky's The Psychology of Art. (December 2020) - Larrain, Antonia; Haye, Andrés
A significant number of articles published in Theory & Psychology have been inspired by, or discuss, Vygotsky's contribution to psychology. However, most of the available publications and discussions on Vygotsky overlook his theory of art and emotions and, more broadly, his view on subjectivity. In this article we offer a reading of Vygotsky's The Psychology of Art . According to our interpretation, art is conceived in this theory as a social technique for (re)constructing life and transforming bodies; human emotions are dialogical processes, culturally and semiotically created, and historically transformed. Our theoretical perspective differs from some other interpretations of Vygotsky's work because of its emphasis on the centrality of emotions in psychological life, and particularly on the intertwining of sociogenesis and microgenesis. Through emotions, discourse practices and cultural techniques have transformative effects on bodily reorganization ( catharsis ) and subjective experience ( perezhivanie ). This is discussed in relation to the political implications of a theory of emotions and its relevance for the theorization of subjectivity.